Analisis Tingkat Kesulitan Soal Try Out Fisika SMA Negeri 5 Banda Aceh - Susanna Susanna; Putri Ani; Abdul Hamid (Department of Physics Education, Universitas Mataram, 2020)
The purpose of this study was to see the difficulty level of physics exam questions at SMA Negeri 5 Banda Aceh in the 2018/2019 academic year. This type of research is a qualitative descriptive study. Those who will be the subjects of this research are students of class XII MIPA at SMA Negeri 5 Banda Aceh for the 2018/2019 academic year, who took the trial test determined by 32 students who were selected by lottery based on the list of participants in the trial test. Furthermore, the object of this research is a matter of trying physics for the 2018/2019 academic year originating from the Aceh provincial education office. The data test technique was carried out using documentation data, namely in the form of test questions for physics testing for the 2018/2019 academic year along with the student test scores. The data obtained were analyzed using the difficulty level formula (difficulty). The results of the data analysis showed that of the 40 items tested, only 7.5% of the items were too easy, 37.5% of the items were easy, 32.5% of the items were medium, 17.5% of the items that came were difficult difficult) and 5% of the answer items are too difficult (difficult). This shows that the physics experimental questions have varying levels of difficulty (difficulty).